Structural bioinformatic studies of eight integral transmembrane NADPH oxidases and their AlphaFold 3 predicted QTY analogs with reduced hydrophobicity - Tutu Hu; Rick Cheng; Edward Chen; Shuguang Zhang (PLoS ONE, 2026)
The NADPH oxidase (NOX) family comprises integral membrane-bound enzymes responsible for generating reactive oxygen species (ROS), with critical roles in immune defense, vascular regulation, and cellular signaling. However, their intrinsic hydrophobicity and membrane association created longstanding challenges for extensive research. In this study, we applied the QTY code – a simple protein design strategy that replaces hydrophobic residues leucine (L), isoleucine (I), valine (V), and phenylalanine (F) with hydrophilic yet structurally compatible residues glutamine (Q), threonine (T) and tyrosine (Y) – to generate QTY analogs of NOX1, NOX2, NOX3, NOX4, NOX5, DUOX1, DUOXA1 and CYBA with reduced hydrophobicity. Using AlphaFold 3, we predicted and superposed the structures of native and QTY-engineered analog proteins. Our results show strong structural resemblance between each pair, with root mean square deviation (RMSD) values below 1Å for six out of eight proteins examined. In addition, QTY substitution significantly reduced surface hydrophobicity, indicating improved water-solubility while preserving 3D structural fold integrity. Our findings demonstrate the potential of QTY-designed NOX variants with reduced hydrophobicity as surrogates for use in structural biology, monoclonal antibody discoveries, drug discovery, and other applications where native membrane proteins present experimental limitations.